2014
DOI: 10.2146/ajhp130221
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine for insomnia: A review of the literature

Abstract: Robust studies evaluating the safety and efficacy of quetiapine for the treatment of insomnia are lacking. Given its limited efficacy data, its adverse-effect profile, and the availability of agents approved by the Food and Drug Administration for the treatment of insomnia, quetiapine's benefit in the treatment of insomnia has not been proven to outweigh potential risks, even in patients with a comorbid labeled indication for quetiapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 36 publications
(54 reference statements)
3
64
1
8
Order By: Relevance
“…30 Prescription rates for all other medications examined remained statistically unchanged except for the overall decline in temazepam. Contrary to reports of substantial prescribing of the antipsychotic quetiapine (Seroquel) for insomnia, [31][32][33][34][35] we found barely discernible rates of use.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…30 Prescription rates for all other medications examined remained statistically unchanged except for the overall decline in temazepam. Contrary to reports of substantial prescribing of the antipsychotic quetiapine (Seroquel) for insomnia, [31][32][33][34][35] we found barely discernible rates of use.…”
Section: Discussioncontrasting
confidence: 99%
“…29,30 In addition, there have been anecdotal reports of off-label prescriptions of low doses (50 mg) of the antipsychotic quetiapine (tradename: Seroquel) for insomnia. [31][32][33][34][35] The objectives of this study are to describe changes in the management rates of insomnia in Australia and to characterize any changes in management actions by FPs over the period 2000 to 2015. Specifically, we aim to:…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews reported a similar paucity of evidence on this topic and a lack of high quality studies, but relied on non-systematic searches (6)(7)(8)10). We conducted a more thorough and explicit search than these reviews.…”
Section: Discussionmentioning
confidence: 99%
“…However, this guideline suggests use may be appropriate in select patients with co-morbid insomnia where other modalities have failed (consensus-based statement). Four non-systematic narrative reviews have been conducted to evaluate the efficacy of quetiapine for insomnia (6)(7)(8)(9) and one 2011 systematic review investigated atypical antipsychotics for various off-label indications (10). Non-systematic narrative reviews may provide a good overview of the topic; yet non-systematic searches increase the possibility of missing relevant evidence.…”
Section: Rationalementioning
confidence: 99%
“…Because of potential adverse effects of quetiapine, in the treatment of insomnia, it is recommended only in patients with specific co-morbid psychiatric disorders. 27 Antihistamines T h e s e d r u g s i n c l u d e O T C s l e e p m e d i c a t i o n s (diphenhydramine, doxylamine and hydroxyzine) and prescription drug doxepin. Blockade of H 1 receptors in the cortex and ventrolateral preoptic nucleus in the hypothalamus turns the sleep-wake switch off.…”
Section: Quetiapinementioning
confidence: 99%